Uncovering the Veil: Overcoming Challenges in Science Teaching Standards - Agni, Raya; Febriawan, Aan; Zainal, Syech (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study examines the challenges faced by junior high school teachers in implementing science teaching standards, with a particular focus on issues related to instructional guidance, continuous assessment, and the provision of resources. It aims to identify gaps and offer strategies to enhance science education quality in Indonesian schools.Methodology: A mixed-method approach was employed, combining classroom observations, structured interviews, and questionnaires. Data were collected from 160 participants, including teachers and students from junior high schools in Mantikulore District, Central Sulawesi. Quantitative data were analyzed using descriptive statistics, while qualitative insights were drawn from thematic coding of interviews and observations.Main Findings: The findings reveal that while teachers demonstrate competence in providing guidance and conducting assessments, significant challenges remain in creating conducive learning environments. These include insufficient access to modern teaching resources, limited training in continuous assessment methods, and overcrowded classrooms that hinder effective science instruction. Students reported that practical activities and hands-on experiments were often constrained by a lack of laboratory materials, impacting their engagement and understanding of scientific concepts.Novelty/Originality of this study: This research provides localized insights into the systemic and practical challenges faced by Indonesian schools in implementing science teaching standards. It uniquely highlights the interplay between resource availability, teacher development, and classroom practices. The study proposes innovative strategies for resource allocation, capacity building, and the integration of technology to address these gaps, contributing to evidence-based policy recommendations.